2008 IEEE 10th Workshop on Multimedia Signal Processing 2008
DOI: 10.1109/mmsp.2008.4665167
|View full text |Cite
|
Sign up to set email alerts
|

Informed stego-systems in active warden context: Statistical undetectability and capacity

Abstract: Several authors have studied stego-systems based on Costa scheme, but just a few ones gave both theoretical and experimental justifications of these schemes performance in an active warden context. We provide in this paper a steganographic and comparative study of three informed stego-systems in active warden context: scalar Costa scheme, trellis-coded quantization and spread transform scalar sosta Scheme. By leading on analytical formulations and on experimental evaluations, we show the advantages and limits … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…Proposed by Eggers [4], he showed that the ST improves the robustness against the AWGN attack. In our previous work [11], we showed the good steganographic performance of the ST-QIM. From Fig.1, we note that the ST-QIM has a better security level than the QIM thanks to using a secret direction.…”
Section: Spread Transform : Alternative Or/and Second Security Layermentioning
confidence: 81%
“…Proposed by Eggers [4], he showed that the ST improves the robustness against the AWGN attack. In our previous work [11], we showed the good steganographic performance of the ST-QIM. From Fig.1, we note that the ST-QIM has a better security level than the QIM thanks to using a secret direction.…”
Section: Spread Transform : Alternative Or/and Second Security Layermentioning
confidence: 81%
“…For the TCQ scheme, it has been shown in [19] that the capacity against an AWGN attack is not as good as that of SCS. In the work presented here, we incorporate ICA into TCQ scheme to improve its performances especially in terms of capacity and robustness.…”
Section: Trellis Coded Quantization and Independent Domainmentioning
confidence: 99%
“…Recently, it has been shown in [19] that the combination of ST with SCS has preserved perfectly the PDF of the host signal. The ST-SCS scheme had the same security level of the TCQ scheme.…”
Section: Trellis Coded Quantization and Independent Domainmentioning
confidence: 99%
See 2 more Smart Citations